No Evidence for the Watching-Eyes Effect on Human Impulsivity - Shinohara, Asami; Yamamoto, Shinya (Frontiers in Psychology, 2018)
People often become more altruistic when they think or feel that someone is watching them. Known as the “watching-eyes effect,” this is argued to be caused by the motivation to gain and maintain a positive social reputation as an altruistic individual (the “reputation seeking” mechanism). However, an alternative mechanism underlying the watching-eyes effect could be that people suppress their impulsive tendency to pursue benefit rather than increase their altruism, and this may lead to apparent increases in altruistic tendencies. This “suppressing impulsivity” mechanism is considered intrapersonal rather than socially mediated which is associated with “reputation seeking.” We examined whether the suppressing impulsivity mechanism would be associated with the watching-eyes effect by measuring participants’ impulsivity in the presence of watching-eyes stimuli. In a controlled experiment, we presented life-size pictures of human faces with a direct gaze on a monitor in front of participants taking part in a time-discounting task. Two types of faces, “in-group” (faces of participants’ classmates) and “out-group” (unfamiliar faces) were presented to examine the effect of social attribution. We used a flower picture as a control stimulus. In the time-discounting task, participants chose one of two options: a small amount of money that they could get immediately or a larger amount of money that they could get after a given time interval. The results showed no significant difference in participants’ time-discount rate regardless of the types of stimuli presented during the time-discount task. A post-task questionnaire confirmed that the participants were aware of the presented stimuli and revealed that they paid more attention to the in-group stimuli than to the out-group and flower stimuli, though this difference in attentive states had no effect on their impulsivity during the task. These results suggest that suppressing impulsivity is not a plausible mechanism for the watching-eyes effect. The null effect for the difference between the in-group and out-group stimuli also supports this conclusion. Thus, it is plausible that the watching-eyes effect is caused by the human tendency to boost social reputation and can be mediated by the social relationship with others.